Liquid Chromatographic Determination of Aromatic Amines in Water Samples after Gold Nanoparticles Coated Membrane Microextraction - Basheer, Chanbasha (Asian Journal of Chemistry, 2020)
A novel microextraction technique was developed for aromatic amines using gold nanoparticles coated membrane. The preparation of the extraction device involves with the synthesis of gold nanoparticles via the reduction of AuCl3 by hydroxyethyl cellulose followed by coating to the polyethersulfone membrane. The simple extraction procedures involved placing the extraction device in a stirred aqueous sample solution, followed by desorption in an organic solvent using ultrasonication. The extract was analyzed by high performance liquid chromatography. Optimal extraction conditions include 50 min extraction time, 20 min desorption time, 30 mL sample volume, sample pH 10, 5 % NaCl content and 17 mg sorbent mass coupled with 100 μL desorption solvent. The performance of the extraction device in the absence and presence of gold nanoparticles was investigated. Enrichment factors ranged from 148 (for 3-nitroaniline) to 200 (for 3,4-dichloroaniline). The calibration results exhibited good linearity (r2 = 0.9931-0.9988) within the range 0.5-20 μg/L. The limits of detection were 0.3-0.7 μg/L and RSDs (n = 6) 10-19%. Comparison was made with solid-phase extraction. The method was subsequently applied to municipal wastewater samples. The proposed microextraction method offers advantages such as easy operation, high recovery, faster extraction, minimal use of organic solvent and elimination of tedious solvent evaporation and reconstitution steps.